Impact of Mikania micrantha H.B.K. Invasion on Diversity and Abundance of Plant Species of Chitwan National Park, Nepal - Shrestha, Binoj Kumar; Dangol, Dharma Raj (Journal of Institute of Science and Technology, 2015)
This research investigated the invasion of the alien plant Mikania micrantha H.B.K. and its impact on plant species richness and abundance in Chitwan National Park (CNP) forest. Stratified sampling technique was used to collect the information using the nested quadrats in the Mikania invaded and not invaded sites in July 2011. The study revealed that the invasion highly related with the vegetation structure of the habitat; higher the tree crown cover lower the invasion. On the other hand, the invasion in terms of cover percent of Mikania irrespective of the biomass (fresh weight) decreased plant species richness. Species richness showed unimodal response to the Mikania cover percent with the decrease after 35% of Mikania cover. Journal of Institute of Science and Technology, 2014, 19(2): 30-36